Serum bile acids concentration in captive American flamingos (Phoenicopterus ruber). (November 2015) - Eshar, D.; Lindemann, D.; Pohlman, L.
Abstract This study was conducted in order to determine serum bile acids concentration in captive American flamingos (Phoenicopterus ruber ). Seventeen healthy flamingos of both sexes were evaluated as part of an overall clinical health assessment. Each bird underwent a complete physical examination, complete blood count, and serum biochemistry testing. Blood samples were collected from the medial metatarsal vein and submitted for a serum bile acids analysis. The median serum bile acids concentration for the American flamingo was 30 μmol/L (min = 20 μmol/L, max = 58 μmol/L), with no significant difference (p  = 0.14) between males and females in this study. The data presented in this report can promote better physiological understanding and improve clinical management of this avian species.